AOT Arising from DC: Report of 5 Rare Cases with IHC and Review of Literature - Ramya, Dr Dasari Ramya; Raghunath, Dr Vandana; Krishna, Dr. Polisetty Siva; Kamal, Dr. Firoz; Kommalapati, Dr Vatsalya; Latha, Dr Aparna (International Journal of Innovative Research in Medical Science, 2024)
Adenomatoid Odontogenic Tumour (AOT) is a rare benign tumour that only occurs in the maxillofacial region, accounting for 3% of all odontogenic tumours. It primarily affects females in their second decade, with a preference for the anterior maxillary region. It is divided into three types: follicular, extrafollicular, and peripheral. Follicular variations involving all four canines account for 60% and 40% of all canine variants, respectively. Dentigerous cyst is an odontogenic cyst that typically develops from impacted mandibular third teeth. The epithelial lining of a Dentigerous cyst may develop into an odontogenic tumour such as ameloblastoma. Adenomatoid odontogenic tumour (AOT) forming as a complication in a dentigerous cyst has been described as a hybrid variety of AOT. We show five such unusual examples including maxillary right premolar, lateral, canine, maxillary left canine, premolar and left deciduous lateral, canine, permanent central, premolars, and first molars in the second, third, fourth, and second decades, respectively. Thus, in this IHC, a Dentigerous cyst (DC) and AOT emerging from DC were compared using a panel of immunohistochemical markers, including cytokeratin (CK) 18 and 19, to explain the differences between the two. We also go over the clinical, radiological, histopathologic, and therapeutic aspects of these instances.